Flexible gallium nitride devices for various applications in internet of things - Ho, Leonard Zhan Lin (Nanyang Technological University, 2023)
Several studies describing the formation and characterization of GaN films for flexible optoelectronic devices have been published. However, the fabrication method and process are not yet illustrated. We describe the steps required to fabricate an MSM PD from a bare substrate, as well as the various strain tests performed on the PET substrate and the changes in the MSM PD when it is illuminated by incident light. This report seeks to determine whether GaN can be utilized as a notable semiconductor material.